13.6k views
4 votes
(a) Use differentiation to find a power series representation forf(x) =1(6 + x)2.f(x) =∞ leftparen1.gif(−1)n(n+1)xn6n+2​ rightparen1.gifsum.gifn = 0What is the radius of convergence, R?R = (b) Use part (a) to find a power series forf(x) =1(6 + x)3.f(x) =∞ leftparen1.gif(−1)n(n+3)(n+1)xn6n+5​ rightparen1.gifsum.gifn = 0What is the radius of convergence, R?R = (c) Use part (b) to find a power series forf(x) =x2(6 + x)3.f(x) =∞ leftparen1.gif(−1)n(n+2)(n+1)xn+26n+3​ rightparen1.gifsum.gifn = 2What is the radius of convergence, R?R =

User Philwb
by
6.2k points

1 Answer

3 votes

(a) Wild guess:


f(x)=\frac1{(6+x)^2

Recall the power series


\displaystyle\frac1{1-x}=\sum_(n=0)^\infty x^n

With some manipulation, we can write


\displaystyle\frac1{6+x}=\frac16\frac1{1-\left(-\frac x6\right)}=\frac16\sum_(n=0)^\infty\left(-\frac x6\right)^n=\sum_(n=0)^\infty((-x)^n)/(6^(n+1))

Take the derivative and we get


\displaystyle-\frac1{(6+x)^2}=-\sum_(n=0)^\infty(n(-x)^(n-1))/(6^(n+1))


\displaystyle=-\sum_(n=1)^\infty(n(-x)^(n-1))/(6^(n+1))


\displaystyle=-\sum_(n=0)^\infty((n+1)(-x)^n)/(6^(n+2))

so we have


\displaystyle\frac1{(6+x)^2}=\sum_(n=0)^\infty((n+1)(-x)^n)/(6^(n+2))

By the ratio test, this series converges if


\displaystyle\lim_(n\to\infty)\left|(((n+2)(-x)^(n+1))/(6^(n+3)))/(((n+1)(-x)^n)/(6^(n+2)))\right|=\left|\frac x6\right|\lim_(n\to\infty)(n+2)/(n+1)=\left|\frac x6\right|<1

or
|x|<6, so that the radius of convergence is
R=6.

(b). If we take the second derivative, we get


\displaystyle\frac2{(6+x)^3}=\sum_(n=0)^\infty(n(n+1)(-x)^(n-1))/(6^(n+2))


\displaystyle=\sum_(n=1)^\infty(n(n+1)(-x)^(n-1))/(6^(n+2))


\displaystyle=\sum_(n=0)^\infty((n+1)(n+2)(-x)^n)/(6^(n+3))


\displaystyle\frac1{(6+x)^3}=\frac12\sum_(n=0)^\infty((n+1)(n+2)(-x)^n)/(6^(n+3))

Apply the ratio test again and we get
R=6.

(c) Multiply the previous series by
x^2 and we get


\displaystyle(x^2)/((6+x)^3)=\frac12\sum_(n=0)^\infty((n+1)(n+2)(-x)^nx^2)/(6^(n+3))


\displaystyle=\frac12\sum_(n=0)^\infty((n+1)(n+2)(-1)^nx^(n+2))/(6^(n+3))

The ratio test yet again tells us
R=6.

User Stevejay
by
7.6k points